SEASONAL MIGRATION AND COLONY BEHAVIOR OF THE TROPICAL HONEYBEE APIS DORSA TA F. (HYMENOPTERA: APIDAE) - Sih Kahono; Koji Nakamura; Moh. Amir (Research Center for Biology, 1999)
A study on seasonal migration of the tropical honeybee, Apis dorsata wasconducted in the protected habitat of the Bogor Botanic Garden, West Jawa, Indonesia by monitoring the arrivals and departures of colonies of the honeybee. The colonies arrived in the garden during both the higher mean monthly rainfall and the lower number of rainy days per month and departed during the time of increasing the number of both total monthly rainfall and monthly rainy days. During their stay in the garden, the colonies occupied a certain location and host plant patches. Their duration of stay in the garden was variable. It was 77%, 9% and 4% of the colonies developed, stable and decreased their colony member, respectively. The colonies (23%) performed reproduction by reproducing new queens. Early arriving colonies stayed in very long periods and reproduced colony fission.